(untitled) (MMIT Proceedings, 2024)
Attracting private investors to the field of preschool education is an important aspect of the modern educational landscape. The article discusses various methods and approaches to attracting private investment in the pre-school educational sphere in order to improve the quality of children’s preparation for school.